CULTURAL SUSTAINABILITY AND SUSTAINABLE TOURISM - ALUKA EVA JOSELYN (UCU, 2024)
The study investigated cultural sustainability and sustainable tourism, focusing on Uganda’s Buganda Royal Palace. The objectives included assessing the significance of cultural sustainability and sustainable tourism, assessing the relationship between cultural sustainability and sustainable tourism, the importance of preserving cultural heritage while promoting sustainable tourism practice as well as the sampling and data collection tools which included interviews and the findings.
A CASE STUDY OF UGANDA'S BUGANDA ROYAL KINGDOM